Embracing the Allelopathic Potential of Invasive Aquatic Plants to Manipulate Freshwater Ecosystems - Reynolds, Sam A.; Aldridge, David C. (Frontiers in Environmental Science, 2021)
Freshwater ecosystems provide essential resources and vital ecosystem services. These ecosystems exist in a delicate state of balance and are under increasing anthropogenic and climatic pressures. One of the major anthropogenic threats to freshwater ecosystems is eutrophication and harmful algal blooms. Current chemical and physical interventions to prevent algal blooms can be expensive, ephemeral and disruptive to other aspects of the ecosystem. Therefore, there is interest in utilising biological methods of control. This study aimed to assess the viability of allelopathic repression of nuisance algae species by invasive aquatic plants. The allelopathic effect of Hydrocotyle ranunculoides (Floating Pennywort) and Crassula helmsii (Swamp Stonecrop) were tested in both whole plant and crushed plant states for their ability to affect the average growth rates of mono-cultures and co-cultures of the green algae Chlorella vulgaris and the cyanobacterium Synechocystis sp. PCC6803. Methanol extracts from these species have been identified in the literature to have high allelopathic potential. The key findings of this study are that, for Chlorella: whole H.ranunculoides and crushed C.helmsii had a negative effect on its average growth rate; whole H.ranunculoides had a greater negative effect than crushed H.ranunculoides; and crushed C.helmsii had a more negative effect than crushed H.ranunculoides. For Synechocystis: crushed C.helmsii had a greater negative effect on its average growth rate than crushed H.ranunculoides; and the presence of Chlorella in co-culture experiments had a universally positive effect on its average growth rate. The species-specific nature of these allelopathic interactions suggests that the use of allelopathy for algal bloom control may have to be assessed on a case by case basis and the use of combination treatments should be assessed. Moreover, the ecological engineering exerted by allelochemicals in open water systems is likely to be direct, indirect and context-specific.